Theoretical and legal problems of the National Police of Ukraine employees` certification - K. H. Harbuziyk; L. V. Mohilevskyi (Law and Safety)
To clarify the essence and content of the concept “certification” a number of general theoretical approaches to the interpretation of this scientific category has been revealed. It has been proposed to understand the certification of employees of the National Police of Ukraine in different meanings: broad and narrow. The key features of attestation have been highlighted, which, in turn, include the fact that it is: 1) a legal procedure that is regulated and carried out primarily on the basis of the legislation, in particular general labor; 2) the procedure for assessing not only the qualifications, but also the business, political, psychological, moral and other qualities of the employee, which one must have to perform the duties; 3) a procedure that entails certain legal consequences in the form of a change or termination of labor relations between the employee and the employer.